Investments in African agricultural research - Pardey, Philip G.; Roseboom, Johannes; Beintema, Nienke M. (International Food Policy Research Institute, 1995)
Over the past three decades the development of agricultural research staff in sub-Saharan Africa has been impressive. Developments in agricultural research expenditures were less positive. Many of the developments of the past decade in personnel, expenditures, and sources of support for public-sector R&D in Africa are not sustainable. The rapid buildup of research staff is not paralleled by an equal growth in financial resources. Spending per scientist has continuously declined during the past 30 years, but most dramatically during the 1980s. Resources are spread increasingly thin over a growing group of researchers, which has negative effects on the efficiency and effectiveness of agricultural research.